Heavy metal speciation and mobility assessment of arid soils in the vicinity of Al Ain landfill, United Arab Emirates. (28th January 2005) - Howari, Fares
Sixty-four surface soil samples taken in the vicinity of Al Ain landfill were analysed for cadmium, chromium, copper, nickel, lead and zinc by inductively coupled plasma spectroscopy. Extraction techniques were used to establish the association of the total concentrations of the six metals in the soil samples with their contents in the exchangeable, carbonate, iron/manganese oxides, and residual fractions. In the investigated soils, the recorded concentrations were as follows: 0.043 mg kg -1 for cadmium, 19.1 mg kg -1 for chromium, 53.3 mg kg -1 for copper, 60 mg kg -1 for nickel, 13.7 mg kg -1 for lead, and 117 mg kg -1 for zinc. Cadmium, chromium, nickel, lead and zinc concentrations in the investigated soil samples reflect the natural background values in shale, whereas copper is slightly enriched. I-geo (geoaccumulation index) values of the metals in the soils under study indicate that they are uncontaminated with cadmium, chromium, nickel, lead and zinc, but contaminated to moderately contaminated with copper. Heavy metal contents in the sediments were found to be significantly influenced by different physico-chemical parameters. The effect of these parameters can be arranged in the following order: clay fraction > carbonate fraction > silt fraction > organic matter fractions. A sequential extraction procedure showed that the total concentrations of the heavy metals are largely bound to the residual phase (retained 71.4% of cadmium, 77.8% of chromium, 75% of copper, 47% of nickel, 62.8% of lead, and 75.8% of zinc). A likely sequence of mobility in the investigated soils is as follows: chromium > lead > nickel > cadmium > zinc > copper.